2007
DOI: 10.1590/s0101-20612007000300006
|View full text |Cite
|
Sign up to set email alerts
|

Estabilidade do néctar misto de cajá e umbu

Abstract: 456 ResumoAs tendências do setor alimentício são ditadas pelo mercado consumidor e seu comportamento social. Atualmente, a busca por produtos saudáveis tem crescido e frutos exóticos estão sendo cada vez mais utilizados visando o fator inovação. O cajá e umbu são frutos bastante comercializados no Norte e Nordeste do Brasil e o desenvolvimento de produtos à base destes frutos mostra ser uma opção interessante, pelo sabor e pelas características de funcionalidade. Elaborou-se um néctar misto que foi submetido à… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
8
0
4

Year Published

2011
2011
2023
2023

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 20 publications
(15 citation statements)
references
References 10 publications
3
8
0
4
Order By: Relevance
“…During storage ( Figure 1A), a significant increase in pH value was observed for all nectar formulations, except for the nectar containing xanthan gum (T2) and guar gum (T3) at 180 days of storage. These results corroborate the results of several authors, including Silva et al [17] , studying the stability of guava juice packed either in glass bottles or carton, and storing for 250 days at room temperature; Mattietto et al [18] study with a blend of cajá and umbu nectar packed in glass bottles for 90 days of storage; Leitão [19] , study with blackberry nectar packed in glass or polypropylene packages and stored either at room temperature or refrigeration; and Carvalho et al [20] , studying a blended beverage consisting of cashew apple juice and coconut water containing caffeine. According to Silva [21] , the increase in pH value during storage may be due to the degradation of ascorbic acid, with respective reduction of free hydrogen ions in the product, which corroborates the findings of this study, once a significant decrease in vitamin C content was observed during storage.…”
Section: Resultssupporting
confidence: 91%
“…During storage ( Figure 1A), a significant increase in pH value was observed for all nectar formulations, except for the nectar containing xanthan gum (T2) and guar gum (T3) at 180 days of storage. These results corroborate the results of several authors, including Silva et al [17] , studying the stability of guava juice packed either in glass bottles or carton, and storing for 250 days at room temperature; Mattietto et al [18] study with a blend of cajá and umbu nectar packed in glass bottles for 90 days of storage; Leitão [19] , study with blackberry nectar packed in glass or polypropylene packages and stored either at room temperature or refrigeration; and Carvalho et al [20] , studying a blended beverage consisting of cashew apple juice and coconut water containing caffeine. According to Silva [21] , the increase in pH value during storage may be due to the degradation of ascorbic acid, with respective reduction of free hydrogen ions in the product, which corroborates the findings of this study, once a significant decrease in vitamin C content was observed during storage.…”
Section: Resultssupporting
confidence: 91%
“…In the case of sugars, the rates were close to those registered by Mattieto, Lopes, and Menezes (2007) for the development of mixed nectar made from umbu and cajá (respectively 14.15; 5.24; 8.91).…”
Section: Physicochemical and Microbiological Analysessupporting
confidence: 74%
“…Entretanto, os valores apresentados na Tabela 2 estão dentro da faixa esperada para produtos à base de frutas (FREITAS et al, 2006;MATTIETTO et al, 2007;CARVALHO et al, 2011;VEGARA et al, 2013).…”
Section: Determinação Da Capacidade Antioxidante Total Pelo Método Dpunclassified